2017
DOI: 10.1158/0008-5472.can-17-2285
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of IDO1 Inhibitors: From Bench to Bedside

Abstract: Small molecule inhibitors of indoleamine 2,3-dioxygenase-1 (IDO1) are emerging at the vanguard of experimental agents in oncology. Here pioneers of this new drug class provide a bench-to-bedside review on preclinical validation of IDO1 as a cancer therapeutic target and on the discovery and development of a set of mechanistically distinct compounds – indoximod, epacadostat and navoximod – that were first to be evaluated as IDO inhibitors in clinical trials. As ‘immunometabolic adjuvants’ to widen therapeutic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
411
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 459 publications
(425 citation statements)
references
References 141 publications
2
411
0
2
Order By: Relevance
“…It has been previously shown that tryptophan depletion by cancer cell-expressed IDO1 could lead to the T cell anergy and activation of immunosuppressive Tregs and MDSCs. 46,47 Currently, drugs targeting IDO1 pathway are in clinical trials to reverse the tumor-induced immunosuppression. 47 In accordance with our data, a recent report demonstrated that restoration of p53 activity via nutlin-3a was able to induce ICD and promote CD8 T cell-dependent anti-tumor immunity in mice bearing EL4 tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously shown that tryptophan depletion by cancer cell-expressed IDO1 could lead to the T cell anergy and activation of immunosuppressive Tregs and MDSCs. 46,47 Currently, drugs targeting IDO1 pathway are in clinical trials to reverse the tumor-induced immunosuppression. 47 In accordance with our data, a recent report demonstrated that restoration of p53 activity via nutlin-3a was able to induce ICD and promote CD8 T cell-dependent anti-tumor immunity in mice bearing EL4 tumor.…”
Section: Discussionmentioning
confidence: 99%
“…46,47 Currently, drugs targeting IDO1 pathway are in clinical trials to reverse the tumor-induced immunosuppression. 47 In accordance with our data, a recent report demonstrated that restoration of p53 activity via nutlin-3a was able to induce ICD and promote CD8 T cell-dependent anti-tumor immunity in mice bearing EL4 tumor. 31 In that study, activated p53 was able to eliminate immunosuppressive MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…226 Finally, several studies aim at testing the safety and therapeutic potential of peptide-based vaccines targeting one single TAA including not only viral antigens like HPV p16, E6 and E7, 227-229 but also shared TAAs like HER2, NY-ESO-1, survivin and telomerase reverse transcriptase (TERT), 161,230-252 as well as TAAs involved in the establishment of immunosuppression, such as PD-L1 and indoleamine 2,3-dioxygenase 1 (IDO1). 253-256 …”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…The concept of IDO1 as an immunosuppressive actor was extended by later discoveries that it was a common pathophysiological mediator of tumoral immune escape [25]. As a classical pharmacological target, IDO was ripe for development of small molecule inhibitors [26] with medicinal chemistry groups at New Link Genetics i and Incyte ii ultimately advancing several mechanistically distinct compounds to clinical trials [27]. Efforts to elucidate IDO1 regulatory and effector pathways discussed below have illuminated its major function as a inflammatory modifier in cancer ( Figure 2) .…”
Section: Ido1 Modifies Inflammation and Immunitymentioning
confidence: 99%
“…Careful examination of the phenotype of Ido1 –/– mice suggests that IDOi may not be free of side-effects but may be much less toxic than immune checkpoint drugs or traditional or targeted chemotherapy [108]. A detailed review on the preclinical discovery and development of the first IDOi to be translated to clinic – indoximod, epacadastat and navoximod – will appear elsewhere [27]. There also have been several excellent comprehensive reviews with detailed surveys of medicinal chemistry, pharmacological and biological considerations [8, 59, 74, 109112].…”
Section: Therapeutic Approaches To Block Ido Functionmentioning
confidence: 99%